Family business resilience in crisis: study case analysis in a collectivist society - Kussudyarsana, Kussudyarsana; Maimun, Muhammad Halim; Maulana, Huda Kurnia; Nugroho, Munajat Tri; Santoso, Budi (Business: Theory and Practice, 2024)
In an era marked by persistent challenges and uncertainties, gaining insights into how family businesses navigate crises becomes imperative. While previous research has delved into the resilience of family firms, there is a notable absence of a comprehensive exploration into how inherent traits in family businesses, particularly within collectivist societies, contribute to their resilience during crises. This study aims to fill this gap and elucidate the distinctive dynamics and behaviours exhibited by family businesses in such cultural contexts. Utilising qualitative case studies and interviews, this research delves into nuanced insights into the dynamic approaches employed by these businesses. The family firms demonstrated adaptability by adjusting their operations and leveraged human resources by seeking support from family members. Additionally, they showcased creativity in enhancing market offerings. The study also reveals unique behaviours, particularly resilience through collaboration with competitors. This research makes an academic contribution by offering insights into the behaviour of family businesses within collectivist cultural contexts during crises. From a practical standpoint, it informs the development of tailored crisis management strategies for family business owners and policymakers, underscoring the significance of collaboration among competitors. The study emphasizes avenues for fostering innovative approaches, promoting resilience, and ensuring sustainability within the ever-evolving business landscape. Furthermore, it establishes a foundation for future explorations, urging further investigation into crisis adaptation strategies tailored to the cultural contexts in which family businesses are situated.